The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s40831-017-0118-4
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability of Permanent Rare Earth Magnet Motors in (H)EV Industry

Abstract: It is clear that hybrid/electric vehicles [(H)EVs] are only as green as the materials and energy that they use. According to MIT, the production and processing of rare earth elements (REEs) found in (H)EVs come with their own hefty environmental price tag (K. Bourzac, ''The Rare-Earth Crisis,'' MIT Technol. Rev., 114(3):58-63, 2011). These damages include radioactive wastewater leaks and 'slash-and-burn processes' required to manufacture and separate REEs. Some life cycle assessment (LCA) studies found that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…Considering the hidden recovery potential of metal material flow, the stability risk of the supply chain can be greatly reduced, particularly for lithium iron phosphate batteries (LiFePO 4 ) and lithium nickel cobalt manganese acid (NMC) [109]. However, there is also a material flow, namely, of permanent magnet rare earth, with low consumption but huge stability and environmental and social risks because of its specific suppliers [100,110].…”
Section: Production Stage Materials Extraction and Collectionmentioning
confidence: 99%
“…Considering the hidden recovery potential of metal material flow, the stability risk of the supply chain can be greatly reduced, particularly for lithium iron phosphate batteries (LiFePO 4 ) and lithium nickel cobalt manganese acid (NMC) [109]. However, there is also a material flow, namely, of permanent magnet rare earth, with low consumption but huge stability and environmental and social risks because of its specific suppliers [100,110].…”
Section: Production Stage Materials Extraction and Collectionmentioning
confidence: 99%
“…Bailey et al (2017) [80] showed that the criticality of rare earth elements for permanent magnets in electric vehicles was higher than for batteries. A constant material supply largely depends on improved recovery and recycling methods.…”
Section: Materials Availability and Criticality Assessment In Battery mentioning
confidence: 99%
“…All of these metals are likely to become scarce in the future, but delay in scaling up EV production would reduce peak and cumulative mining requirements, and would also allow time to develop a capability to recycle Nd and Dy from vehicle motors. At present, there is essentially no capability for recycling of Li from vehicles or of Nd and Dy from electric motors of any kind, and recycling of Nd and Dy would be very difficult, as discussed by Bailey et al (2017) .…”
Section: Vehicle Performance Potential and Regulationsmentioning
confidence: 99%